Solar Cells
By introducing fullerene or fullerene derivatives as intermediate layers into tin perovskite solar cells, the problem of low open circuit voltage of tin perovskite solar cells is solved, and the effect of improving open circuit voltage and conversion efficiency is achieved.
Patent Information
- Application Number
- CN201910591939.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-10
- Filing Date
- 2019-07-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-07-02
AI Technical Summary
The open circuit voltage of tin-based perovskite solar cells is low, resulting in a lower actual conversion efficiency than that of lead-based perovskite solar cells.
The perovskite compound represented by the chemical formula ASnX3 is used as the light absorption layer, and fullerene or fullerene derivatives are introduced as intermediate layers, such as C60-SAM, to weaken the interaction between the tin-based perovskite compound and the electron transport material, thereby reducing the depth of the interface defect level.
By introducing an intermediate layer of fullerene or fullerene derivative, the open circuit voltage of the tin-based perovskite solar cell is improved, the electron transportability of the light absorption layer is enhanced, the carrier inactivation is reduced, and the conversion efficiency of the solar cell is improved.
Smart Images

Figure CN110707217B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solar cells. Background Art
[0002] In recent years, research and development of perovskite solar cells have been ongoing. Perovskite solar cells use a 3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) as a light absorbing material.
[0003] Non-patent document 1 discloses using a light absorbing material of a perovskite solar cell having a chemical formula of CsSnI 3 The perovskite compound represented by the invention uses TiO as the electron transport material. 2 , and an organic semiconductor called Spiro-OMETAD is used as a hole transport material.
[0004] Non-patent document 2 discloses using a light absorbing material of a perovskite solar cell having a chemical formula of CH 3 NH 3 PbI 3-x Cl x Represents a perovskite compound.
[0005] Prior Art Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-025170
[0007] Non-Patent Document 1: Mulmudi Hemant Kumar and 12 others, “Lead-free halideperovskite solar cells with high photocurrents realized through vacancy modulation”, Advanced Materials, (UK), November 2014, Vol. 26, No. 41, pp. 7122-7127
[0008] Non-Patent Document 2: Agnese Abrusci and five others, "High-Performance Perovskite-Polymer Hybrid Solar Cells via Electronic Coupling with Fullerene Monolayers", Nano Letter, (UK), June 2013, Vol. 13, pp. 3124-3128 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The object of the present disclosure is to provide a tin-based perovskite solar cell with a further improved open circuit voltage.
[0011] Means for solving problems
[0012] The solar cell disclosed in the present invention comprises a first electrode, a second electrode, a light absorbing layer, and an intermediate layer.
[0013] The light absorbing layer is located between the first electrode and the second electrode.
[0014] The intermediate layer is located between the light absorbing layer and at least one electrode selected from the first electrode and the second electrode.
[0015] The light absorbing layer contains a composition of ASnX 3 (wherein A is a monovalent cation and X is a halogen anion),
[0016] The intermediate layer is in contact with the light absorbing layer,
[0017] At least one electrode selected from the first electrode and the second electrode has light transmittance, and
[0018] The intermediate layer contains at least one selected from 4-(1′,5′-dihydro-1′-methyl-2′H-[5,6]fullerene-C60-Ih-[1,9-c]pyrrol-2′-yl)benzoic acid and fullerene C60.
[0019] Effects of the Invention
[0020] The present disclosure provides a tin-based perovskite solar cell with a further improved open circuit voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a graph showing the measured values of conversion efficiency of the lead-based perovskite solar cell and the tin-based perovskite solar cell prepared by the present inventors.
[0022] Figure 2A It is shown that the TiO 2 As the electron transport layer, the lead perovskite compound CsPbI 3 As a light absorbing layer, and at the interface between the electron transport layer and the light absorbing layer, CsPbI 3 When Pb vacancies are introduced, the electronic state density calculation results obtained by the first principle calculation method are used.
[0023] Figure 2B It is shown that the TiO 2As the electron transport layer, the tin perovskite compound CsSnI 3 As a light absorbing layer, and at the interface between the electron transport layer and the light absorbing layer, CsSnI 3 When Sn vacancies are introduced, the electronic state density calculation results obtained by the first principle calculation method are used.
[0024] Figure 3 A cross-sectional view showing a solar cell according to an embodiment.
[0025] Figure 4 A cross-sectional view showing a modified example of the solar cell according to the embodiment.
[0026] Figure 5 The analysis results of C60 of the solar cells of Examples and Comparative Examples obtained by time-of-flight secondary ion mass spectrometry (ie, TOF-SIMS) are shown. DETAILED DESCRIPTION
[0027] <Definition of terms>
[0028] The term "perovskite compound" as used in this specification refers to a compound having the chemical formula ABX 3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and a perovskite crystal structure represented by the above-mentioned and a crystal structure similar thereto.
[0029] The term "tin-based perovskite compound" used in this specification refers to a perovskite compound containing tin.
[0030] The term "tin-based perovskite solar cell" used in this specification refers to a solar cell containing a tin-based perovskite compound as a light absorbing material.
[0031] The term "lead-based perovskite compound" used in this specification refers to a perovskite compound containing lead.
[0032] The term "lead-based perovskite solar cell" used in this specification refers to a solar cell containing a lead-based perovskite compound as a light absorbing material.
[0033] <Embodiments of the present disclosure>
[0034] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings.
[0035] Figure 3 A cross-sectional view of a solar cell 100 according to an embodiment is shown.
[0036] like Figure 3As shown, the solar cell 100 according to the embodiment includes a first electrode 2, a second electrode 7, a light absorbing layer 5, and an intermediate layer 4. The light absorbing layer 5 is located between the first electrode 2 and the second electrode 7. The intermediate layer 4 is located between the light absorbing layer 5 and at least one electrode selected from the first electrode 2 and the second electrode 7. Figure 3 In the embodiment, the intermediate layer 4 is located between the light absorbing layer 5 and the first electrode 2. The intermediate layer 4 may also be located between the light absorbing layer 5 and the second electrode 7. The solar cell 100 involved in the embodiment may have two intermediate layers 4. One intermediate layer 4 is located between the light absorbing layer 5 and the first electrode 2, and the other intermediate layer 4 is located between the light absorbing layer 5 and the second electrode 7. The intermediate layer 4 is in direct (i.e., physical) contact with the light absorbing layer 5. The intermediate layer 4 and the light absorbing layer 5 are arranged between the first electrode 2 and the second electrode 7 so that the first electrode 2 and the second electrode 7 are opposite to each other. At least one electrode selected from the first electrode 2 and the second electrode 7 is light-transmitting. In this specification, "the electrode is light-transmitting" means that more than 10% of light at any wavelength in the light with a wavelength of 200 to 2000 nm passes through the electrode.
[0037] The solar cell 100 according to the embodiment may further include an electron transport layer 3 located between the light absorbing layer 5 and the first electrode 2 . In this case, the intermediate layer 4 may be located between the light absorbing layer 5 and the electron transport layer 3 .
[0038] The solar cell 100 according to the embodiment may further include a hole transport layer 6 located between the light absorbing layer 5 and the second electrode 7. In this case, the intermediate layer 4 may be located between the light absorbing layer 5 and the hole transport layer 6. The solar cell 100 according to the embodiment may include a substrate 1. The first electrode 2 is provided on the substrate 1.
[0039] (Light absorbing layer 5)
[0040] The light absorbing layer 5 contains a light absorbing material having a chemical formula of ASnX 3 (wherein A is a monovalent cation and X is a halogen anion). The monovalent cation located at the A site is not limited. Examples of monovalent cations include organic cations or alkali metal cations. Examples of organic cations include methylammonium cations (i.e., CH 3 NH 3 + ), formamidinium cation (NH 2 CHN 2 +), phenethylammonium cation (i.e. C 6 H 5 CH 2 CH 2 NH 3 +) or guanidine Cations (i.e. CH 6 N3 + Examples of alkali metal cations include cesium cations (Cs + ). The monovalent cation at the A site is preferably a carboxamidinium cation. The monovalent cation at the A site may also be composed of two or more cations. An example of a halogen anion at the X site is an iodide ion. The halogen anion at the X site may also be composed of two or more halogen ions.
[0041] The light absorbing layer 5 may contain materials other than the light absorbing material. For example, the light absorbing layer 5 may further contain a material for reducing the chemical formula ASnX 3 A quenching substance that can represent the defect density of the perovskite compound. The quenching substance includes a fluoride such as tin fluoride. The molar ratio of the quenching substance to the light absorbing material can be 5% or more and 20% or less.
[0042] As described above, the light absorbing layer 5 contains the chemical formula ASnX 3 The light absorbing layer 5 may mainly contain a perovskite compound represented by the chemical formula ASnX 3 Here, the light absorbing layer 5 mainly contains a perovskite compound represented by the chemical formula ASnX 3 The term "perovskite compound" means that the light absorbing layer 5 contains 70 mass % or more of the chemical formula ASnX 3 The light absorbing layer 5 may also contain 80% by mass or more of the perovskite compound. The light absorbing layer 5 may also contain the perovskite compound represented by the chemical formula ASnX 3 The light absorbing layer 5 may contain impurities.
[0043] The thickness of the light absorbing layer 5 is, for example, 100 nm to 10 μm. Alternatively, the thickness of the light absorbing layer 5 may be 100 nm to 1000 nm. The thickness of the light absorbing layer 5 depends on the light absorption of the light absorbing layer 5. The light absorbing layer 5 may be formed by a coating method using a solution.
[0044] (Middle layer 4)
[0045] The intermediate layer 4 contains at least one selected from fullerene and fullerene derivatives. Fullerene includes fullerene C60 (i.e., buckminsterfullerene). Fullerene derivatives include 4-(1',5'-dihydro-1'-methyl-2'H-[5,6]fullerene-C60-Ih-[1,9-c]pyrrol-2'-yl)benzoic acid (hereinafter referred to as "C60-SAM"). The mass spectrum of the intermediate layer 4 may have a first peak at a mass number of 720.
[0046] C60-SAM has a greater voltage-enhancing effect than [6,6]-phenyl-C61-butyric acid methyl ester (hereinafter referred to as "PCBM"). This is because the SAM part is chemically adsorbed on the oxide surface as the electron transport layer, so the in-plane coverage of C60 is improved. In the case of PCBM, there is no such adsorption, so PCBM does not dissolve when the perovskite solution is applied, resulting in a decrease in coverage and a reduced effect.
[0047] The intermediate layer 4 may contain tin element.
[0048] In the intermediate layer 4, the ratio of carbon to tin (i.e., the value equal to (the number of moles of carbon atoms / the number of moles of tin atoms)) can be 35% or more and 408% or more, or 51% or more and 110% or less. The molar ratio is calculated based on the measurement results using X-ray photoelectron spectroscopy.
[0049] When the intermediate layer 4 includes C60-SAM, the molar ratio of carbon to tin may be 51% or more and 263% or less, or 51% or more and 109% or less.
[0050] When the intermediate layer 4 contains fullerene C60, the molar ratio of carbon to tin may be 74% to 408%, or 74% to 212%.
[0051] When the molar ratio of carbon to tin is within the above range, a high open circuit voltage can be achieved.
[0052] In the region determined as the intermediate layer region, when the measurement by X-ray photoelectron spectroscopy can be performed at only one point due to the relationship between the measurement limit of the measuring device and the thickness of the intermediate layer 4, the molar ratio of carbon to tin in the intermediate layer 4 refers to the molar ratio calculated from the measurement result of the one point. In the region determined as the intermediate layer 4 region, when the measurement by X-ray photoelectron spectroscopy can be performed at multiple points, the molar ratio of carbon to tin in the intermediate layer 4 is the average value of the molar ratios calculated from the multiple measurement results.
[0053] The thickness of the intermediate layer 4 is, for example, greater than 0.7 nm and less than 10 nm. In the present embodiment, the region of the intermediate layer 4 in the solar cell is determined as follows. The solar cell is etched along the thickness direction from the main surface of the solar cell, and the elemental composition of the surface exposed by etching is determined by X-ray spectroscopy. The region where the molar amount of the perovskite compound contained in the light absorbing layer 5 obtained based on the result of the X-ray spectroscopy is approximately the same as the molar amount of the material constituting the layer adjacent to the light absorbing layer 5 across the intermediate layer 4 is determined as the region of the intermediate layer 4. The molar amount of the perovskite compound contained in the light absorbing layer 5 can be obtained, for example, using the molar number of the tin element determined by X-ray spectroscopy. The molar amount of the material constituting the layer adjacent to the light absorbing layer 5 across the intermediate layer 4 can be obtained using the molar number of a specific element (hereinafter referred to as "the first element") constituting the adjacent layer determined by X-ray spectroscopy. Since the intermediate layer 4 is determined in this way, even when the intermediate layer 4 is very thin, the region where the intermediate layer 4 is provided can be determined. The layer adjacent to the light absorbing layer 5 via the intermediate layer 4 may be, for example, the electron transport layer 3, or a layer other than the electron transport layer 3 such as a porous layer described later. For example, the light absorbing layer 5, the intermediate layer 4, and the electron transport layer 3 are sequentially arranged in contact with each other, and the electron transport layer 3 is composed of TiO 2 In the case of a structure in which the light absorbing layer 5 is adjacent to the light absorbing layer 5 via the intermediate layer 4, a region where approximately the same molar amount of tin and titanium selected as the first element is detected by X-ray spectroscopy is determined to be the intermediate layer 4. In the case where oxygen is selected as the first element, a region where 1 / 2 of the molar amount of oxygen and approximately the same molar amount of tin are detected is determined to be the intermediate layer 4. "Approximately the same molar amount" means that the difference in molar amount (mol %) is 10 mol % or less. The first element used when identifying the intermediate layer 4 is determined from the elements constituting the layer adjacent to the light absorbing layer 5 via the intermediate layer 4 as follows. If the element constituting the layer adjacent to the light absorbing layer 5 via the intermediate layer 4 is one type, the element is the first element. In the case where the layer adjacent to the light absorbing layer 5 via the intermediate layer 4 contains a plurality of elements, for example, the element with the highest decomposition energy in X-ray spectroscopy can be selected as the first element. For example, in the case where the layer adjacent to the light absorbing layer 5 via the intermediate layer 4 is composed of TiO 2 In the case of the electron transport layer 3 composed of Ti, the decomposition energy of Ti as a metal element is higher than that of O as a light element. Therefore, in this case, Ti is selected as the first element.
[0054] (Substrate 1)
[0055] The substrate 1 holds the first electrode 2, the intermediate layer 4, the light absorbing layer 5, and the second electrode 7. The substrate 1 can be formed of a transparent material. Examples of the substrate 1 include a glass substrate or a plastic substrate. Examples of the plastic substrate include a plastic film. When the first electrode 2 has sufficient strength, the first electrode 2 holds the intermediate layer 4, the light absorbing layer 5, and the second electrode 7, so the solar cell 100 does not need to have the substrate 1.
[0056] (First electrode 2 and second electrode 7)
[0057] The first electrode 2 and the second electrode 7 are conductive. At least one of the first electrode 2 and the second electrode 7 is light-transmissive. Light in the visible region to the near-infrared region can pass through the light-transmissive electrode. The light-transmissive electrode can be formed of a transparent and conductive material.
[0058] Examples of such materials are:
[0059] (i) titanium oxide doped with at least one selected from lithium, magnesium, niobium and fluorine,
[0060] (ii) gallium oxide doped with at least one selected from tin and silicon,
[0061] (iii) gallium nitride doped with at least one selected from silicon and oxygen,
[0062] (iv) indium-tin composite oxide,
[0063] (v) tin oxide doped with at least one selected from antimony and fluorine,
[0064] (vi) zinc oxide doped with at least one selected from boron, aluminum, gallium and indium, or
[0065] (vii) Complexes thereof.
[0066] The light-transmitting electrode can also be formed by setting a light-transmitting pattern using an opaque material. As the light-transmitting pattern, for example, a linear, wavy line, a lattice, and a punched metal-like pattern formed by a plurality of fine through holes arranged regularly or irregularly can be cited. If the light-transmitting electrode has these patterns, light can be transmitted through the part where the electrode material is not present. As the opaque material, for example, platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc and an alloy containing any of these metals can be cited. In addition, a conductive carbon material can also be used.
[0067] In the case where the solar cell 100 does not have the electron transport layer 3, the first electrode 2 is formed of, for example, a material having a barrier property for holes from the light absorption layer 5. In this case, the first electrode 2 is not in ohmic contact with the light absorption layer 5. The barrier property for holes from the light absorption layer 5 refers to the property of only allowing electrons generated in the light absorption layer 5 to pass through and not allowing holes to pass through. The Fermi level of the material having a barrier property for holes is higher than the energy level at the top of the valence band of the light absorption layer 5. The Fermi level of the material having a barrier property for holes may be higher than the Fermi level of the light absorption layer 5. An example of a material having a barrier property for holes is aluminum. In the case where the solar cell 100 has an electron transport layer 3 between the light absorption layer 5 and the first electrode 2, the first electrode 2 may not have a barrier property for holes from the light absorption layer 5. In this case, the first electrode 2 may be in ohmic contact with the light absorption layer 5.
[0068] In the case where the solar cell 100 does not have a hole transport layer 6, the second electrode 7 is formed of, for example, a material having a barrier property for electrons from the light absorption layer 5. In this case, the second electrode 7 is not in ohmic contact with the light absorption layer 5. The barrier property for electrons from the light absorption layer 5 refers to the property of only allowing holes generated in the light absorption layer 5 to pass through and not allowing electrons to pass through. The Fermi level of the material having a barrier property for electrons is lower than the energy level at the bottom end of the conduction band of the light absorption layer 5. The Fermi level of the material having a barrier property for electrons may be lower than the Fermi level of the light absorption layer 5. Examples of materials having a barrier property for electrons include carbon materials such as platinum, gold, or graphene. In the case where the solar cell 100 has a hole transport layer 6 between the light absorption layer 5 and the second electrode 7, the second electrode 7 may not have a barrier property for electrons from the light absorption layer 5. In this case, the second electrode 7 may be in ohmic contact with the light absorption layer 5.
[0069] The material having a blocking property for holes from the light absorbing layer 5 may not be light-transmitting. The material having a blocking property for electrons from the light absorbing layer 5 may not be light-transmitting. Therefore, when the first electrode 2 or the second electrode 7 is formed using these materials, the first electrode 2 or the second electrode 7 has the above-mentioned pattern that allows light to pass through the first electrode 2 or the second electrode 7.
[0070] The light transmittance of each of the first electrode 2 and the second electrode 7 may be 50% or more, or 80% or more. The wavelength of light transmitted through the electrodes depends on the absorption wavelength of the light absorbing layer 5. The thickness of each of the first electrode 2 and the second electrode 7 is, for example, in the range of 1 nm or more and 1000 nm or less.
[0071] (Electron transport layer 3)
[0072] The electron transport layer 3 includes a semiconductor. The electron transport layer 3 may be formed of a semiconductor having a band gap of 3.0 eV or more. By forming the electron transport layer 3 from a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light can be transmitted to the light absorbing layer 5. Examples of semiconductors include organic or inorganic n-type semiconductors.
[0073] Examples of organic n-type semiconductors include imide compounds, quinone compounds, fullerenes or fullerene derivatives. Examples of inorganic n-type semiconductors include metal oxides, metal nitrides or perovskite oxides. Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO is preferred. 2 An example of a metal nitride is GaN. An example of a perovskite oxide is SrTiO 3 or CaTiO 3 .
[0074] The electron transport layer 3 may be formed of a material having a band gap greater than 6.0 eV. Examples of materials having a band gap greater than 6.0 eV include (i) halides of alkali metals or alkaline earth metals such as lithium fluoride or calcium fluoride, (ii) alkaline earth metal oxides such as magnesium oxide, or (iii) silicon dioxide. In this case, in order to ensure the electron transport property of the electron transport layer 3, the thickness of the electron transport layer 3 may be, for example, less than 10 nm.
[0075] The electron transport layer 3 may include a plurality of layers formed of different materials.
[0076] (Hole Transport Layer 6)
[0077] The hole transport layer 6 is composed of an organic substance or an inorganic semiconductor. Representative examples of organic substances used for the hole transport layer 6 include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyaniline)9,9'-spirobifluorene (hereinafter referred to as "spiro-OMeTAD"), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT"), poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT"), or copper phthalocyanine (hereinafter referred to as "CuPC").
[0078] Examples of inorganic semiconductors are Cu 2 O、CuGaO 2 、CuSCN、CuI、NiO x 、MoO x 、V 2 O 5 Or carbon materials like graphene oxide.
[0079] The hole transport layer 6 may include a plurality of layers formed of different materials.
[0080] The thickness of the hole transport layer 6 may be greater than 1 nm and less than 1000 nm, may be greater than 10 nm and less than 500 nm, or may be greater than 10 nm and less than 50 nm. If the thickness of the hole transport layer 6 is greater than 1 nm and less than 1000 nm, sufficient hole transport properties can be exhibited. In addition, if the thickness of the hole transport layer 6 is greater than 1 nm and less than 1000 nm, since the resistance of the hole transport layer 6 is low, light can be converted into electricity with high efficiency.
[0081] The hole transport layer 6 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent stabilize the holes in the hole transport layer 6 .
[0082] Examples of supporting electrolytes include ammonium salts or alkali metal salts. Examples of ammonium salts include tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazole Salt or pyridine Examples of alkali metal salts include lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF 6 , LiBF 4 , lithium perchlorate or potassium tetrafluoroborate.
[0083] The solvent contained in the hole transport layer 6 may have high ion conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilization of the solute, an organic solvent is preferred. Examples of organic solvents include heterocyclic compounds such as tert-butylpyridine, pyridine, or N-methylpyrrolidone.
[0084] The solvent contained in the hole transport layer 6 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The ionic liquid is preferred in terms of low volatility and high flame retardancy.
[0085] Examples of ionic liquids are 1-ethyl-3-methylimidazole Imidazoles such as tetracyanoborates compounds, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds or azoamine compounds.
[0086] (Effects of solar cells)
[0087] Next, the basic effects of the solar cell 100 are described. When the solar cell 100 is irradiated with light, the light absorbing layer 5 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 3 via the intermediate layer 4. On the other hand, the holes generated in the light absorbing layer 5 move to the hole transport layer 6. The electron transport layer 3 is connected to the first electrode 2, and the hole transport layer 6 is connected to the second electrode 7, so that current is taken out from the first electrode 2 acting as a negative electrode and the second electrode 7 acting as a positive electrode.
[0088] (Method of Manufacturing Solar Cell 100)
[0089] The solar cell 100 can be manufactured, for example, by the following method.
[0090] First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (hereinafter referred to as "CVD") or sputtering. Then, the electron transport layer 3 is formed on the first electrode 2 by sputtering.
[0091] Next, an intermediate layer 4 is formed on the electron transport layer 3. Examples of methods for forming the intermediate layer 4 include a coating method or a deposition method. The coating method is described below. First, a solution containing at least one selected from fullerenes and fullerene derivatives and an organic solvent is prepared. Examples of organic solvents include chlorobenzene, toluene, dimethyl sulfoxide (hereinafter referred to as "DMSO") or N,N-dimethylformamide (hereinafter referred to as "DMF"). The concentration of at least one selected from fullerenes and fullerene derivatives may be greater than 0.01 mg / mL and less than 10 mg / mL, or may be greater than 0.1 mg / mL and less than 5 mg / mL. The solution is applied to the electron transport layer 3 by spin coating. Then, the applied solution is heated, for example, at a temperature of greater than 80°C and less than 160°C. Thus, the intermediate layer 4 is obtained.
[0092] Next, a light absorbing layer 5 is formed on the intermediate layer 4. The light absorbing layer 5 can be formed by, for example, the following method. As an example, a layer containing (HC(NH 2 ) 2 ) 1-y (C 6 H 5 CH 2 CH 2 NH 3 ) y Sn 3 (where 0<y<1, hereinafter sometimes referred to as “FA 1- y PEA y Sn 3 ”) is described below.
[0093] First, SnI was added to the organic solvent. 2 HC(NH 2 ) 2 I (hereinafter referred to as "FAI") and C 6 H 5 CH 2 CH 2 NH 3 I (hereinafter referred to as "PEAI") to obtain a mixed solution. An example of the organic solvent is a mixed solution of DMSO and DMF (the volume ratio of DMSO:DMF=1:1).
[0094] Sn 2 The molar concentration may be 0.8 mol / L or more and 2.0 mol / L or less, or 0.8 mol / L or more and 1.5 mol / L or less.
[0095] The molar concentration of FAI may be 0.8 mol / L or more and 2.0 mol / L or less, or 0.8 mol / L or more and 1.5 mol / L or less.
[0096] The molar concentration of PEAI may be 0.1 mol / L or more and 0.5 mol / L or less, or 0.1 mol / L or more and 0.3 mol / L or less.
[0097] Next, the mixed solution is heated to a temperature of 40 degrees Celsius or higher and 180 degrees Celsius or lower by a heating device. 2 , FAI and PEAI to prepare a mixed solution. The obtained mixed solution is then placed at room temperature.
[0098] Next, the mixed solution is applied to the electron transport layer 3 by spin coating to form a coating film. Then, the coating film is heated at a temperature of 40° C. to 100° C. for 15 minutes to 1 hour. Thus, the light absorbing layer 5 is obtained. When the mixed solution is applied by spin coating, a poor solvent may be added dropwise during the spin coating. Examples of the poor solvent include toluene, chlorobenzene, or diethyl ether.
[0099] The mixed solution may contain a quenching substance such as tin fluoride. The concentration of the quenching substance may be 0.05 mol / L or more and 0.4 mol / L or less. The quenching substance suppresses the generation of defects in the light absorbing layer 5. The causes of the generation of defects in the light absorbing layer 5 include, for example, Sn 4 + The increase in the amount of Sn leads to an increase in Sn voids.
[0100] A hole transport layer 6 is formed on the light absorbing layer 5. Examples of methods for forming the hole transport layer 6 include coating and printing. Examples of coating methods include blade coating, rod coating, spray coating, dip coating, or spin coating. Examples of printing methods include screen printing. The hole transport layer 6 may be obtained by mixing a plurality of materials, and then the hole transport layer 6 may be pressurized or fired. When the material of the hole transport layer 6 is an organic low molecular weight substance or an inorganic semiconductor, the hole transport layer 6 may be prepared by vacuum evaporation.
[0101] Finally, the second electrode 7 is formed on the hole transport layer 6. In this way, the solar cell 100 is obtained. The second electrode 7 can be formed by a CVD method or a sputtering method.
[0102] Figure 4 A cross-sectional view showing a modified example of the solar cell 200 according to the present embodiment. Figure 3 Unlike the solar cell 100 shown, the solar cell 200 includes a porous layer 8 .
[0103] Figure 4 In the solar cell 200 shown, a first electrode 2, an electron transport layer 3, a porous layer 8, an intermediate layer 4, a light absorption layer 5, a hole transport layer 6, and a second electrode 7 are sequentially stacked on a substrate 1. The porous layer 8 includes a porous body. The porous body includes pores. The solar cell 200 may not have the substrate 1. The solar cell 200 may not have the hole transport layer 6.
[0104] (Porous layer 8)
[0105] The pores in the porous layer 8 are connected from the portion in contact with the intermediate layer 4 to the portion in contact with the electron transport layer 3. The pores in the porous layer 8 can be filled with the material of the intermediate layer 4. In addition, the material of the intermediate layer 4 can reach the surface of the electron transport layer 3 via the pores in the porous layer 8. The material of the light absorbing layer 5 is arranged on the porous layer 8 and in the pores in the porous layer 8 via the intermediate layer 4. In other words, the porous layer 8, the intermediate layer 4 and the light absorbing layer 5 are stacked in this order. Therefore, the light absorbing layer 5 is not in direct contact with the electron transport layer 3, and electrons move from the light absorbing layer 5 to the electron transport layer 3 via the intermediate layer 4.
[0106] The porous layer 8 makes it easy to form the light absorbing layer 5. The intermediate layer 4 formed on the porous layer 8, for example, covers the surface and pore walls of the porous layer 8. Since the thickness of the intermediate layer 4 is small, the shape of the surface and pores of the porous layer 8 is maintained. In this case, the material of the light absorbing layer 5 also intrudes into the pores of the porous layer 8 covered by the intermediate layer 4. Therefore, the material of the light absorbing layer 5 is difficult to be repelled or agglomerated on the surface of the intermediate layer 4. Therefore, the porous layer 8 becomes a support for the light absorbing layer 5, and the light absorbing layer 5 can be formed into a uniform film. The light absorbing layer 5 can be formed by applying a solution on the intermediate layer 4 by spin coating and then heating it.
[0107] Light is scattered by the porous layer 8. Therefore, the optical path length of light passing through the light absorbing layer 5 can be increased. The increase in the optical path length can increase the amount of electrons and holes generated in the light absorbing layer 5.
[0108] The solar cell 200 can be produced by the same method as the solar cell 100. The porous layer 8 is formed on the electron transport layer 3 by, for example, a coating method.
[0109] The porous layer 8 serves as a base when forming the light absorbing layer 5 . The porous layer 8 does not inhibit light absorption by the light absorbing layer 5 . The porous layer 8 also does not inhibit electron movement from the light absorbing layer 5 to the electron transport layer 3 via the intermediate layer 4 .
[0110] As described above, the porous layer 8 includes a porous body. Examples of porous bodies include porous bodies formed by connecting insulating or semiconductor particles. Examples of materials for insulating particles include aluminum oxide or silicon oxide. Examples of materials for semiconductor particles include inorganic semiconductors. Examples of inorganic semiconductors include metal oxides (including perovskite oxides), metal sulfides or metal chalcogenides. Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO is preferred. 2 Examples of perovskite oxides are SrTiO 3 or CaTiO 3 Examples of metal sulfides include CdS, ZnS, In 2 S 3 、SnS、PbS、Mo 2 S.WS 2 , Sb 2 S 3 、Bi 2 S 3 、ZnCdS 2 Cu 2 S. Examples of metal chalcogenides (i.e., metal selenides) include CdSe, CsSe, In 2Se 3 ,WSe 2 , HgSe, SnSe, PbSe or CdTe.
[0111] The thickness of the porous layer 8 can be greater than 0.01 μm and less than 10 μm, or greater than 0.1 μm and less than 1 μm. The surface roughness of the porous layer 8 can be relatively large. Specifically, the surface roughness coefficient given by the effective area / projected area can be greater than 10, or greater than 100. Furthermore, the projected area refers to the area of the shadow formed at the rear when the object is irradiated with light from the front. The effective area refers to the actual surface area of the object. The effective area can be calculated based on the volume obtained from the projected area and thickness of the object, and the specific surface area and volume density of the material constituting the object. The specific surface area is measured, for example, by the nitrogen adsorption method.
[0112] Next, the basic effects of the solar cell 200 are described. When the solar cell 200 is irradiated with light, the light absorbing layer 5 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 3 via the intermediate layer 4. On the other hand, the holes generated in the light absorbing layer 5 move to the hole transport layer 6. As described above, the electron transport layer 3 is connected to the first electrode 2, and the hole transport layer 6 is connected to the second electrode 7. Thus, current is taken out from the first electrode 2 acting as a negative electrode and the second electrode 7 acting as a positive electrode.
[0113] <Foundation that forms the basis of this disclosure>
[0114] The findings that form the basis of the present disclosure are as follows.
[0115] The theoretical conversion efficiency of tin-based perovskite solar cells is high, but the actual conversion efficiency is lower than that of lead-based perovskite solar cells. Figure 1 It is a graph showing the measured values of the conversion efficiency of the lead-based perovskite solar cell and the tin-based perovskite solar cell made by the present inventor. The lead-based perovskite solar cell and the tin-based perovskite solar cell have a laminated structure of substrate / first electrode / electron transport layer / porous layer / light absorption layer / hole transport layer / second electrode. The details of the lead-based perovskite solar cell and the tin-based perovskite solar cell are described below.
[0116] <Lead-based perovskite solar cells>
[0117] Substrate: Glass substrate
[0118] First electrode: A mixture of indium-tin composite oxide (ITO) and antimony-doped tin oxide (ATO)
[0119] Electron transport layer: dense TiO 2(c-TiO2)
[0120] Porous layer: Mesoporous TiO 2 (mp-TiO2)
[0121] Light absorption layer: HC(NH 2 ) 2 PbI 3
[0122] Hole transport layer: spiro-OMeTAD (2,2',7,7'-tetrakis-(N,N-dimethoxyaniline)9,9'-spirobifluorene)
[0123] Second electrode: Gold
[0124] <Tin-based perovskite solar cells>
[0125] Substrate: Glass substrate
[0126] First electrode: A mixture of indium-tin composite oxide (ITO) and antimony-doped tin oxide (ATO)
[0127] Electron transport layer: dense TiO 2 (c-TiO2)
[0128] Porous layer: Mesoporous TiO 2 (mp-TiO2)
[0129] Light absorption layer: HC(NH 2 ) 2 Sn 3
[0130] Hole transport layer: PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine])
[0131] Second electrode: Gold
[0132] Depend on Figure 1 It can be seen that the open circuit voltage in the tin-based perovskite solar cell is lower than that in the lead-based perovskite solar cell. This is the main reason why the conversion efficiency of the tin-based perovskite solar cell is lower than that of the lead-based perovskite solar cell. As the reason for the reduction in open circuit voltage, it is believed that there is a deep defect energy level of the tin-based perovskite compound at the interface between the electron transport layer and the tin-based perovskite compound, and carriers recombine at this energy level.
[0133] In tin-based perovskite solar cells, unlike lead-based perovskite solar cells, there are more defects at the interface between the electron transport layer and the light absorption layer. The reason is that tin-based perovskite compounds are materials that easily generate Sn voids and have more defects than lead-based perovskite compounds. When defects are generated at the interface between the electron transport layer and the light absorption layer, due to the strong interaction between the electron transport material and the tin-based perovskite compound, a deep recombination energy level is formed at the interface between the electron transport layer and the light absorption layer.
[0134] Figure 2A It shows that TiO 2 As the electron transport layer, the lead perovskite compound CsPbI 3 As a light absorbing layer, and at the interface between the electron transport layer and the light absorbing layer, CsPbI 3 Calculation results of the electron state density obtained by first principle calculation when Pb vacancies are introduced.
[0135] Figure 2B It shows that TiO 2 As the electron transport layer, the lead perovskite compound CsSnI 3 As a light absorbing layer, and at the interface between the electron transport layer and the light absorbing layer, CsSnI 3 Calculation results of the electron state density obtained by first principle calculation when Sn vacancies are introduced.
[0136] Figure 2A and 2B In the experiment, the energy level of the top of the valence band of the perovskite compound is set to 0 eV, and the bottom of the conduction band of the perovskite compound, TiO 2 The top of the valence band and TiO 2 The energy level at the bottom end of the conduction band of the perovskite compound is expressed as a relative value to the energy level at the top end of the valence band of the perovskite compound.
[0137] Depend on Figure 2B It is known that, due to the formation of Sn voids at the interface between the electron transport layer and the light absorption layer, a deep defect level is formed at the center between the top of the valence band and the bottom of the conduction band of the tin-based perovskite compound.
[0138] Specifically, due to the generation of Sn vacancies, the remaining I atoms are strongly bonded to the Ti atoms and stabilized, and the 3d orbital (Ti-3d orbital) of the Ti atoms forming the conduction band at the interface between the electron transport layer and the light absorption layer changes.
[0139] As a result, a deep defect level is formed at the center between the top of the valence band and the bottom of the conduction band of the tin-based perovskite compound due to the changed energy level of the Ti-3d orbital.
[0140] On the other hand, according to Figure 2ACompared with tin-based perovskite compounds, lead-based perovskite compounds have weaker interaction with electrons in electron transport materials, and the defect energy level formed by Pb vacancies becomes a defect energy level shallower than the center between the top of the valence band and the bottom of the conduction band.
[0141] If a deep defect level is generated in a tin-based perovskite compound, electrons in the conduction band and holes in the valence band may relax at the defect level, causing carrier deactivation. On the other hand, if a shallow defect level is generated in a lead-based perovskite compound, the probability of relaxation between electrons and holes is low.
[0142] Therefore, the presence of defect levels is unlikely to contribute to the deactivation of carriers. Therefore, interface defects are a problem unique to tin-based perovskite compounds.
[0143] On the basis of the above, by making the defect level of the tin-based perovskite compound at the interface shallower, the open circuit voltage of the tin-based perovskite solar cell can be increased.
[0144] The inventors have found that it is difficult to generate deep defect levels by introducing fullerenes or fullerene derivatives between the electron transport layer and the light absorption layer. Specifically, it has been found that fullerenes and fullerene derivatives have a weak interaction with tin-based perovskite compounds, and it is difficult to generate deep defect levels in tin-based perovskite compounds even when in contact with tin-based perovskite compounds.
[0145] (Example)
[0146] The present disclosure is described in more detail with reference to the following examples.
[0147] [Example 1]
[0148] In Example 1, the following preparation was performed Figure 3 A solar cell 100 is shown.
[0149] Preparation of SnO with indium doped surface 2 Glass substrate (made by Nippon Sheet Glass Co., Ltd.). Glass substrate and SnO 2 The layers respectively function as a substrate 1 and a first electrode 2. The glass substrate has a thickness of 1 mm.
[0150] On the first electrode 2, a titanium oxide layer having a thickness of about 10 nm was formed as the electron transport layer 3 by sputtering.
[0151] A chlorobenzene solution (200 mL) with a C60-SAM concentration of 0.1 mg / mL was dripped onto the electron transport layer 3. The solution was then spread on the electron transport layer 3 by spin coating. The solution was fired on a hot plate maintained at 120 degrees Celsius. Thus, the intermediate layer 4 was formed.
[0152] Next, SnI was added to the mixed solvent of DMSO and DMF. 2 、SnF 2 、FAI(i.e. HC(NH 2 ) 2 I) and PEAI (i.e. C 6 H 5 CH 2 CH 2 NH 3 I) to obtain a mixed solution. The volume ratio of DMSO:DMF in the mixed solvent is 1:1. SnI 2 、SnF 2 The concentrations of FAI, PEAI and FAI were 1.5 mol / L, 0.15 mol / L, 1.5 mol / L and 0.3 mol / L, respectively.
[0153] In the glove box, the mixed solution (80 μL) was dropped onto the intermediate layer 4 by spin coating to obtain a coating film. The interior of the glove box was filled with N 2 , the oxygen concentration is below 0.1ppm.
[0154] Then, the coating film is fired on a hot plate maintained at 80 degrees Celsius. In this way, the light absorbing layer 5 is formed. The light absorbing layer 5 mainly contains a composition formula of FA 0.83 PEA 0.17 Sn 3 of perovskite compounds.
[0155] Next, in a glove box, a toluene solution (80 μL) containing PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) at a concentration of 10 mg / mL was dropped onto the light absorbing layer 5 by spin coating to form a hole transporting layer 6 .
[0156] Finally, a gold film with a thickness of 100 nm was deposited on the hole transport layer 6 to form the second electrode 7. In this way, the tin-based perovskite solar cell of Example 1 was obtained.
[0157] [Determination of Intermediate Layer 4 and Molar Ratio of Carbon to Tin in Intermediate Layer 4]
[0158] The molar ratio of carbon to tin in the intermediate layer 4 was measured using an X-ray photoelectron spectroscopy analyzer (PHI 5000Versa-Probe II: manufactured by ULVAC-PHI). Specifically, the solar cell of Example 1 was etched along the thickness direction from the main surface of the second electrode 7, and the elemental composition of the surface exposed by etching was measured by the X-ray spectrometry method using the device. The etching was performed by a sputtering method using argon gas. The area where the titanium element and the tin element were detected in approximately the same molar amount was determined as the area of the intermediate layer 4. The molar ratio of carbon to tin in the area of the intermediate layer 4 determined in this way was determined based on the results of X-ray spectrometry using the above-mentioned device. The measurement sample was not exposed to the atmosphere, but was placed in N 2 Transport in atmosphere.
[0159] [TOF-SIMS Analysis of Intermediate Layer 4]
[0160] The present inventors used a time-of-flight secondary ion mass spectrometer (manufactured by ION-TOF, Germany, trade name: TOF.SIMS5-200) to analyze C60 based on time-of-flight secondary ion mass spectrometry (hereinafter referred to as "TOF-SIMS method") to determine whether the region of the intermediate layer 4 determined as described above contains fullerene or a fullerene derivative.
[0161] The etching is performed by sputtering.
[0162] As a sputtering ion source, GCIB (Gas Cluster Ion Beam) was used.
[0163] The test sample is not exposed to the atmosphere but is kept in N 2 Transport in atmosphere.
[0164] Figure 5 The TOF-SIMS spectrum of negative ions in Example 1 is shown. Figure 5 The TOF-SIMS spectra of negative ions in Example 5 and Comparative Example 1 described later are also shown.
[0165] exist Figure 5 In the mass spectrum shown, the peak at mass number 720 is derived from the fullerene group of C60. Figure 5 In the mass spectrum shown, the horizontal axis represents the mass-to-charge ratio (m / z). However, in this example, the charge number is 1 (z=1), so the value of (m / z) represents the value of the mass number (m value).
[0166] [Fluorescence lifetime]
[0167] The fluorescence lifetime of the light absorbing layer 5 contained in the solar cell of Example 1 was measured by photoluminescence measurement using a near-infrared fluorescence lifetime measuring device (C7990: Hamamatsu Photonics). A 532nm YAG laser was used as an excitation laser. The measurement was carried out under the conditions of an observation wavelength of 890nm, an excitation output of 0 to 50mW, and a peak count of 1000. The laser was incident in the direction toward the electron transport layer 3, and the fluorescence returned in this direction was measured to measure the defect density of the perovskite compound on the surface portion of the electron transport layer 3 side of the light absorbing layer 5. Only the portion that was not affected by the superposition of the laser time waveform pulses was taken out, and the fluorescence decay curve A=A was fitted using the least squares method. 0 exp(-t / t)(where A, A 0 and t represent fluorescence intensity, component intensity and time respectively), calculate the fluorescence lifetime t.
[0168] The test sample is not exposed to the atmosphere. 2 The measurement sample is transported and measured in the atmosphere.
[0169] [Open circuit voltage]
[0170] The solar cell of Example 1 was irradiated with an illumination of 100 mW / cm 2 The current-voltage characteristics were measured under simulated sunlight. The open circuit voltage of the solar cell of Example 1 was obtained based on the stabilized current-voltage characteristics. The measurement was carried out at room temperature. The measurement sample was not exposed to the atmosphere and was placed in N 2 The measurement sample is transported and measured in the atmosphere.
[0171] [Example 2]
[0172] In Example 2, the experiment was conducted in the same manner as in Example 1, except that the concentration of C60-SAM contained in the chlorobenzene solution was 0.5 mg / mL.
[0173] [Example 3]
[0174] In Example 3, the experiment was conducted in the same manner as in Example 1, except that the concentration of C60-SAM contained in the chlorobenzene solution was 1.0 mg / mL.
[0175] [Example 4]
[0176] In Example 4, the experiment was conducted in the same manner as in Example 1 except that fullerene C60 was deposited on the electron transport layer 3 to form the intermediate layer 4 in a thickness of 1 nm instead of applying the chlorobenzene solution containing C60-SAM by spin coating.
[0177] [Example 5]
[0178] In Example 5, the experiment was conducted in the same manner as in Example 1 except that fullerene C60 was deposited to a thickness of 5 nm on the electron transport layer 3 to form the intermediate layer 4 instead of applying the chlorobenzene solution containing C60-SAM by spin coating.
[0179] [Example 6]
[0180] In Example 6, the experiment was conducted in the same manner as in Example 1 except that fullerene C60 was deposited to a thickness of 10 nm on the electron transport layer 3 to form the intermediate layer 4 instead of applying the chlorobenzene solution containing C60-SAM by spin coating.
[0181] [Comparative Example 1]
[0182] In Comparative Example 1, the experiment was conducted in the same manner as in Example 1, except that the chlorobenzene solution containing C60-SAM was not applied by spin coating (that is, the intermediate layer 4 was not formed).
[0183] [Comparative Example 2]
[0184] In Comparative Example 2, the same experiment as in Example 1 was conducted except that the intermediate layer 4 was formed by spin coating an ethanol solution containing 4-fluorobenzoic acid at a concentration of 0.2 mol / L instead of spin coating a chlorobenzene solution containing C60-SAM.
[0185] [Comparative Example 3]
[0186] In Comparative Example 3, the experiment was conducted in the same manner as in Example 1 except that the intermediate layer 4 was formed by spin coating an ethanol solution containing glycine at a concentration of 0.2 mol / L instead of spin coating a chlorobenzene solution containing C60-SAM.
[0187] The results of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1 below.
[0188]
Table 1
[0189]
[0190] From the comparison between Comparative Example 1 and Examples 1 to 6, it is found that the open circuit voltage of the solar cell can be increased by providing the intermediate layer 4 containing at least one selected from C60-SAM and fullerene 60.
[0191] As demonstrated in Examples 1 to 3, when the intermediate layer 4 contains C60-SAM and the molar ratio of carbon to tin in the intermediate layer 4 is 51% or more and 109% or less, a high open circuit voltage is obtained.
[0192] From the comparison between Comparative Example 1 and Examples 1 to 3, it can be seen that the fluorescence lifetime is increased by providing the intermediate layer 4 containing C60-SAM. This indicates that the intermediate layer 4 containing C60-SAM makes the defect level of the perovskite compound on the surface of the electron transport layer 3 side of the light absorbing layer 5 shallower, resulting in a reduction in recombination loss.
[0193] Non-patent document 2 discloses that in a solar cell using a lead-based perovskite compound as a material for the light absorbing layer, a C60-SAM layer is provided between the light absorbing layer and the electron transporting layer. However, unlike tin-based perovskite compounds, in lead-based perovskite compounds, defects are less likely to occur at the interface between the light absorbing layer and the electron transporting layer. Figure 2A and Figure 2B As explained, when a lead-based perovskite compound generates defects of Pb voids, the defect energy level itself is relatively shallow. Therefore, the lead-based perovskite solar cell does not have the problem of voltage reduction caused by the deactivation of the carrier when the perovskite compound generates defects. Therefore, the lead-based perovskite solar cell does not have the problem of voltage reduction caused by the defects of the perovskite, which is a problem of the tin-based perovskite solar cell. In other words, the problem solved by C60-SAM in the lead-based perovskite solar cell is different from the problem of the tin-based perovskite solar cell, i.e., the solar cell disclosed in the present invention.
[0194] As reported in non-patent literature 2, in a lead-based perovskite solar cell, by using C60-SAM as an electron transport layer, the energy difference between the electron transport layer and the bottom of the conduction band of the light absorption layer is reduced. Thus, it is possible to reduce the energy barrier when electrons move from the light absorption layer to the electron transport layer. Thus, the C60-SAM provided in the lead-based perovskite solar cell reduces the fluorescence lifetime of the solar cell. In contrast, as shown in Table 1, in the solar cell disclosed in the present invention, by providing an intermediate layer containing C60-SAM, the fluorescence lifetime of the solar cell is increased. From this result, it can be seen that in a tin-based perovskite solar cell, C60-SAM exerts an effect different from that provided in a lead-based perovskite solar cell. Specifically, in a tin-based perovskite solar cell, a fullerene derivative is introduced between a tin-based perovskite compound and an electron transport material, and it is found that the interaction between the electrons of the tin-based perovskite compound and the electron transport material is weakened, and no deep interface defect energy level is generated between the top of the valence band and the bottom of the conduction band, that is, the effect of shallowing the defect energy level. In tin-based perovskite solar cells, since there is no deep energy level between the top of the valence band and the bottom of the conduction band, the process of electron deactivation via this energy level can be suppressed, thereby improving the characteristics.
[0195] As demonstrated in Examples 4 to 6, a high open circuit voltage can be obtained when the intermediate layer 4 contains fullerene C60 and the molar ratio of carbon to tin in the intermediate layer 4 is 74% or more and 408% or less. When the molar ratio is 74% or more and 212% or less (see Examples 4 and 5), a higher open circuit voltage can be obtained.
[0196] From the comparison between Comparative Example 1 and Comparative Examples 2 and 3, it can be seen that the open circuit voltage is reduced when an intermediate layer using a compound that does not contain a fullerene group is provided. This is because the compounds used in Comparative Examples 2 and 3 interact with Sn atoms in the tin-based perovskite compound, unlike fullerenes and fullerene derivatives, to increase the deep defect energy levels from the Sn gap. In addition, the compounds used in Comparative Examples 2 and 3 have poor electronic conductivity, so the voltage taken out is reduced. As described above, by using fullerenes and fullerene derivatives that have little interaction and high electronic conductivity, the open circuit voltage can be increased.
[0197] Industrial Availability
[0198] The solar cell disclosed in the present invention can be used as a solar cell installed on a roof, for example.
[0199] Description of Reference Numerals
[0200] 1 substrate
[0201] 2 1st electrode
[0202] 3 Electron transport layer
[0203] 4 Middle Layer
[0204] 5 Light absorption layer
[0205] 6 Hole Transport Layer
[0206] 7. Second electrode
[0207] 8 Porous layer
[0208] 100, 200 Solar cells
Claims
1. A solar cell comprising a first electrode, a second electrode, a light absorbing layer and an intermediate layer, The light absorbing layer is located between the first electrode and the second electrode. The intermediate layer is located between the light absorbing layer and at least one electrode selected from the first electrode and the second electrode. The light absorbing layer contains a perovskite compound represented by a composition formula ASnX3, wherein A is a monovalent cation, and X is a halogen anion, The intermediate layer is in contact with the light absorbing layer, At least one electrode selected from the first electrode and the second electrode has light-transmitting property, The intermediate layer contains at least one selected from 4-(1',5'-dihydro-1'-methyl-2'H-[5,6]fullerene-C60-Ih-[1,9-c]pyrrol-2'-yl)benzoic acid and fullerene C60 and a tin element, and in the intermediate layer, the molar ratio of carbon to tin is greater than 35% and less than 408%.
2. The solar cell according to claim 1, The mass spectrum of the intermediate layer has a first peak at a mass number of 720.
3. The solar cell according to claim 1, The intermediate layer contains 4-(1',5'-dihydro-1'-methyl-2'H-[5,6]fullerene-C60-Ih-[1,9-c]pyrrol-2'-yl)benzoic acid, In the intermediate layer, the molar ratio of carbon to tin is 74% or more and 408% or less.
4. The solar cell according to claim 1, The intermediate layer contains fullerene C60, and In the intermediate layer, the molar ratio of carbon to tin is 51% or more and 109% or less.
5. The solar cell according to claim 1, In the intermediate layer, the molar ratio of carbon to tin is 51% or more and 110% or less.
6. The solar cell according to any one of claims 1 to 5, An electron transport layer is further provided between the light absorbing layer and the first electrode. The intermediate layer is located between the light absorbing layer and the electron transporting layer. 7 . The solar cell according to claim 1 , further comprising a hole transport layer between the light absorbing layer and the second electrode.
Citation Information
Patent Citations
Photoelectric conversion element consisting of organic-inorganic hybrid structure
JP2016025170A